Molecular Detection of BRCA1 and BRCA2 Mutation in Breast Cancer Patients in Erbil Using PCR Techniques - Hamad, Gihan H.S.; Jubrael, Jaladet M. S.; Ali, Salah A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Breast Cancer is one of the leading causes of death in women and It is known that one quarter of women are expected to develop breast cancer at some ages of their lives. Mutations of breast cancer susceptibility genes 1 and 2 (BRCA1 and BRCA2) are the most well recognized gene mutations responsible for an increased risk of developing breast cancer. This investigation was carried out on 50 patients (all were females) who were diagnosed as breast cancer patients attended Nanakali and Rzgari Hospital in Erbil. This study was planned to detect the probable occurrence of three founder breast cancer mutations in female patients by the use of PCR technique. The outcome of genetic analysis indicated that the percentage of 185del AG mutation was 50 (1 patients) whereas, the percentage of 5382ins C mutation was 50 (4 patients) in BRCA1 gene and the third mutation 6174del T in BRCA2 not detected in any patient from 50 samples. The study demonstrated that the frequency of BRCA1 mutation (10%) was higher than BRCA2 (0%) in this sample of Kurdistan women with breast cancer.
Keywords: BRCA1; BRCA2; breast cancer; Erbil; mutation; PCR technique